Speciation of phosphorus in reduced tillage systems: placement and source effect. - Khatiwada, Raju (Kansas State University, 2011)
Phosphorus (P) management in reduced tillage systems has been a great concern for farmers. Conclusive results for benefits of deep banding of P fertilizers for plant yield in reduced tillage system are still lacking. Knowledge of the dominant solid P species present in soil following application of P fertilizers and linking that to potential P availability would help us to design better P management practices. The objectives of this research were to understand the influence of placement (broadcast- vs. deep band-P or deep placed-P), fertilizer source (granular- versus liquid-P), and time on reaction products of P. Greenhouse and field based experiments were conducted to study P behavior in soils. Soil pH, resin extractable P, total P, and speciation of P were determined at different distances from the point of fertilizer application at 5 weeks (greenhouse and field) and 6 months (field) after P application (at rate 75 kg/ha) to a soil system that was under long-term reduced tillage. X-ray absorption near edge structure spectroscopy technique was used to speciate reaction products of fertilizer P in the soil. The reaction products of P formed upon addition of P fertilizers to soils were found to be influenced by soil pH, P placement methods, and P sources. Acidic pH (below~5.8) tended to favor formation of Fe-P and Al-P like forms whereas slightly acidic near neutral pH soils favored formation of Ca-P like forms. Scanning electron microscope with energy dispersive X-ray analysis of applied fertilizer granules at 5-wk showed enrichment of Al, Fe and Ca in granule- indicating these elements begin to react with applied P even before granules dissolve completely. The availability of an applied P fertilizer was found to be enhanced as a result of the deep banding as compared to the surface broadcasting or deep placed methods. Deep banded liquid MAP was found to be in more adsorbed P like forms and resulted greater resin extractable P both at 5 wk and 6 month after application. Deep banding of liquid MAP would most likely result both agronomically and environmentally efficient solution for no-till farmers.
Keywords: Phosphorus; Phosphorus speciation; Reduced tillage; Phosphorus placement; X-ray absorption near edge structure spectroscopy; Resin extractable phosphorus; Agriculture, General (0473); Agronomy (0285); Biogeochemistry (0425); Chemistry, Agricultural (0749); Environmental Sciences (0768); Plant Sciences (0479); Soil Sciences (0481)